PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI F SMA NEGERI 3 PADANG - Pratiwi, Maharani; Suherman, Suherman (Departemen Matematika, 2024)
Teaching pupils arithmetic problems helps them develop a real-world problem-solving approach. Field findings show that SMA Negeri 3 Padang class XI F students struggle with math. A problem-based learning strategy can solve this. This study investigates how problem-based learning affects mathematical problem-solving. This descriptive, quasi-experimental research uses a nonequivalent posttest only control group design. This study included 2023–2024 SMA Negeri 3 Padang class XI F students. Upon analyzing research hypothesis testing using quizzes and final tests, the P-value <0.05 and average quiz increased. Thus, the problem-based learning methodology affects math problem-solving.Keywords– Mathematical Problem Solving, Hands-On Learning, Problem Based Learning